PATOGENISITAS Salmonella enterica SEROTIPE enteritidis ISOLAT LOKAL PADA ANAK AYAM DAN MENCIT - Kusumaningsih, Ani (BERITA BIOLOGI, 2011)
This study was to identify the pathogenicity of local isolates of Salmonella enterica serotipe enteritidis (S. enteritidis/SE) in experimental chickens and mice. Thirty six local isolates of S. enteritidis isolated from chickens, eggs and human was inoculated 8 intra peritoneally (ip) to each 5 chickens and mice per group. Each group received 0.2 ml of broth culture containing 2 x 10Ã CFU of S. enteritidis. Chickens and mice were observed daily at 1, 2, 3, 4, 5, 6 and 7 days after inoculation for clinical signs and mortality. The result showed that the overall mortality rate of chicken and mice were 78.4% and 63.9% respectively. The highest mortality rate was in the first day after inoculation, 51.1% for chickens and 40.0% for mice, however the lowest mortality rate was in the sixth day (0.0%) after inoculation in chickens and in the seventh day (0.6%) in mice. The bacteria of S. enteritidis can be isolated from various organs (liver, heart and spleen) and caeca tonsil of every dead chickens and mice. The study showed that local isolates of S. enteritidis isolated from chickens, eggs, and human were very pathogen for experimental chickens and mice.